Cracking susceptibility evaluation of some stone fruit species (Sour cherries – Prunus cerasus L.; Sweet cherries – Prunus avium and European plums – Prunus domestica L.) grown in Hungary - Simon, G.; Vágány, É.; Komma, L. (International Journal of Horticultural Science, 2014)
The rain induced fruit cracking is a big, serious problem especially for sweet cherry growers but in some year growers of other stone fruit species had also problem with fruit cracking caused by too much and heavy rainfalls in the ripening and harvesting season. Cracked stone fruits can be easily infected by different diseases like Monillinia sp. Cracked and infected fruits can not be transported for long distance and using for preservation, they lost their market value by the destroyed fruit quality. It was decided to make a research work to determine the rain fruit cracking susceptibility of few stone fruit species (sour cherries, sweet cherries and European plums). Fruit cracking tests were occurred under laboratory conditions on the most common cultivars grown in Hungary. Furthermore we tried to find correlation between the fruit cracking and some fruit quality parameters (fruit size; total sugar content, fruit flesh firmness).Our conclusions are the followings:Sour cherries: There were found differences in the cracking ratio and the cracking dynamics of the tested sour cherry varieties when they were immersed in distillated water for 24 hours. Based on cracking test results under laboratory condition (immersing in distillated water) we made the grouping by cracking susceptibility of sour cherry varieties. Tested cultivars were divided three groups: very susceptible; susceptible; moderately susceptible (tolerant). Groups with varieties are: Very susceptible - ’Maliga emléke’, ’Piramis’, ’Érdi jubileum’,’Érdi nagygyümölcsû’ and ’Meteor korai; Susceptible (Sensitive) – ’Érdi bôtermô’, ’Pándy’ and Cigány 59. Moderately susceptible (tolerant) – ‘Éva’ and ‘Petri’as new rereleases. The most of tested sour cherry varieties are in agreement with the literature (Apostol, 2003) and four of them (’Maliga emléke’, ’Pándy 279’, ‘Éva’ and ‘Petri’) had higher average fruit weight than was mentioned in the literature (Apostol, 2003). Our fruit cracking results are in agreement with Zelinski’s (1964) and Christensen’s (1975) conclusions that there is no close relationship between fruit size and rain induced fruit cracking tendency. We found significant differences between the sugar content of tested cultivars. In contrast of Verner & Blodget (1931) our results confirm Tucker’s opinion that the sugar content is not correlation with the cracking tendency of cherry fruits (Tucker, 1934). Fruits firmness (elasticity) was measured by destructive method when juice was coming out from fruits. There were found big differences of fruit firmness and skin strength of observed cultivars. Our results are only partly agreement with Christensen’s (1996) opinion that cherry cultivars with firmer fruits are more prone to fruit cracking than softer ones. By this was seemingly we did not found close relationship between the fruit firmness and the cracking tendency of sour cherry fruits. We found that during fruits immersing in distillated water the fruit weight was increasing due to the absorbed water. Our opinion is that there is no close relationship between the scale of fruit cracking and the quantity of absorbed water. By results presented above we our opinion is that no very close relationship between the fruit cracking of sour cherries and the observed parameters (fruit size, fruit firmness, sugar content, amount of absorbed water) maybe other varietal effects and physiological characters (fruit skin structural parameters) play more important role in the fruit cracking mechanism of cherries.Sweet cherries: Similarly to sour cherries in the case of sweet cherries we also did not find close relationship between observed fruit parameters and cracking index. It was differences in the cracking ratio and the cracking dynamics of the tested sweet cherry cultivars when they were immersed in distillated water for 24 hours. It was found that the cracking ratio of very cracking susceptible sour cherry varieties had the same or higher cracking index than observed sweet cherries. It is in contrast with the general opinion (Chistensen, 1996) that sour cherries are less prone to rain induced fruit cracking than sweet cherries. We found differences between the cracking ration and cracking dynamic of the same cultivar in different years (2006 and 2013). It is in agreement Christensen’s (1996) opinion that the year effect cause big differences in the fruit cracking of cherries.European plums: We found differences in the cracking ratio and the cracking dynamics of the tested plum varieties when they were immersed in distillated water for 24 hours. A shorter term (6 hours) immersing in water caused three groups by their cracking susceptibility: „Very susceptible”: ’Révfülöpi’ and ’Szarvasi’; „Susceptible”: ’Besztercei’; „Less sensitive”: ’Bluefre’ and ’Cacanska rodna’. A longer term (24 hours) immersing in water resulted only two groups with significant differences: „Susceptible group”: ’Révfülöpi’, ’Szarvasi’ and ’Besztercei’; „Less sensitive”: ’Bluefre’ and ’Cacanska rodna’ Similarly the cherries we did not find correlation between the fruit size and cracking susceptibility of European plum cultivars. It was based on: the big fruit sized ‘Bluefre’ and middle sized ‘Cacanska rodna’ cracked in the lowest scale, during the small sized ’Révfülöpi’, ’Szarvasi’ and ’Besztercei’ cultivars cracked in higher scale We found positive correlations between the cracking susceptibility and total sugar content of tested plum cultivars. Cultivars with significantly lower sugar content (‘Bluefre’ and ‘C. rodna’) showed lower fruit cracking susceptibility than cultivars (’Révfülöpi’, ’Szarvasi’ and ’Besztercei’) with higher sugar content). We found close relationship between the relative (%) absorbed water amount and the fruit cracking susceptibility. Cultivars with higher absorbed water amount (’Szarvasi’-’Révfülöpi’-’Besztercei’) had higher cracking susceptibility.